What personality types dominate among nurses and paramedics: A scoping review?. (December 2020) - Mason, Rod; Roodenburg, John; Williams, Brett
Highlights: Nurse and paramedic personnel experience significant exposure to severe stress levels associated with the high frequency of critical incidents endemic to their professions. Certain personality traits captured by the Big Five framework have been shown to play an important role in predicting burnout in response to stressors, with evidence they reflect a relationship to psychological resilience. There is good reason therefore to seek to understand the distribution to such traits among nurses and paramedics and whether it is typical or atypical. Nurses and paramedics identified as scoring high on Neuroticism and lower on Extraversion may be considered to be less suited to their profession, particularly where they will be exposed to critical incidents. Knowledge of these vulnerabilities could prove useful during selection, and in designing bespoke interventions. Abstract: Background: Certain personality traits captured by the Big Five framework have been shown to play an important role in predicting burnout in response to stressors, with evidence they reflect a relationship to psychological resilience. Understanding such distributions can subsequently serve to facilitate identification and implementation of more specifically targeted preventative strategies. Methods: Arksey and O'Malley's five stage scoping was used to review the literature. The research question that guided this scoping was: Big Five personality factor predominance's among nurses and paramedics, and any relationships with constructs critical for wellbeing. Five electronic databases were searched during November 2018: PsycINFO, Embase, Medline, ProQuest and Scopus. Results: Eighteen articles met inclusion criteria. Two broad themes emerged: those specifically about personality traits of nurses and/or paramedics, and those concerned with various associations between one or other construct and personality trait(s). Low Neuroticism and higher Extraversion are considered desirable traits in nurses and paramedics as they have each been found to have a negative correlation with burnout. Conclusions: Nurses and paramedics with higher Neuroticism and lower Extraversion suggest being less suited to their profession, particularly when exposed to critical incidents.